Childhood absence epilepsy: Behavioral, cognitive, and linguistic comorbidities - Caplan, Rochelle; Siddarth, Prabha; Stahl, Lesley; Lanphier, Erin; Vona, Pamela; Gurbani, Suresh; Koh, Susan; Sankar, Raman; Shields, W. Donald (Epilepsia (Copenhagen), 2008)
Summary Purpose:  Evidence for a poor psychiatric, social, and vocational adult outcome in childhood absence epilepsy (CAE) suggests long‐term unmet mental health, social, and vocational needs. This cross‐sectional study examined behavioral/emotional, cognitive, and linguistic comorbidities as well as their correlates in children with CAE. Methods:  Sixty‐nine CAE children aged 9.6 (SD = 2.49) years and 103 age‐ and gender‐matched normal children had semistructured psychiatric interviews, as well as cognitive and linguistic testing. Parents provided demographic, seizure‐related, and behavioral information on their children through a semi‐structured psychiatric interview and the child behavior checklist (CBCL). Results:  Compared to the normal group, 25% of the CAE children had subtle cognitive deficits, 43% linguistic difficulties, 61% a psychiatric diagnosis, particularly attention deficit hyperactivity disorder (ADHD) and anxiety disorders, and 30% clinically relevant CBCL broad band scores. The most frequent CBCL narrow band factor scores in the clinical/borderline range were attention and somatic complaints, followed by social and thought problems. Duration of illness, seizure frequency, and antiepileptic drug (AED) treatment were related to the severity of the cognitive, linguistic, and psychiatric comorbidities. Only 23% of the CAE subjects had intervention for these problems. Conclusions:  The high rate of impaired behavior, emotions, cognition, and language and low intervention rate should alert clinicians to the need for early identification and treatment of children with CAE, particularly those with longer duration of illness, uncontrolled seizures, and AED treatment.